Increases in graminoids after three decades of change in the High Arctic - James A. Schaefer (Polar Research, 2023)
Climate change portends serious implications for Arctic vegetation. Understanding these effects is likely to be enhanced with long-term observations from permanent plots. I evaluated three decades of change in tundra vegetation from 80 permanent plots on south-eastern Victoria Island, Nunavut, Canada. I compared baseline (1991 and 1992) and contemporary (2019 and 2022) periods in the cover and frequency of graminoids, mosses and common species of forbs, shrubs and lichens. I found substantial shifts in cover of several species and growth forms—an increase in graminoids, decreases in Dryas integrifolia, Polygonum viviparum and Saxifraga oppositifolia, and marginally significant declines in mosses and Cassiope tetragona, but no detectable changes in other groups. The decline in Dryas integrifolia was more pronounced at lower elevations and was noticeable as patches of apparent mortality, inside the plots and elsewhere. The shifts in species abundance were not significantly correlated with each other, nor with changes in soil depth. These changes, manifest as communities with more abundant graminoids, are consistent with expected climate change effects in colder regions of the Arctic. Repeated observations of permanent plots can aid in detecting and understanding long-term ecological change.